Levels of DEFA1, Progranulin, and NRG4 in Patients with Autonomic Neuropathy: Potential Biomarkers for Diagnosis and Prognosis - Diana Nikolova; Zdravko Kamenov; Julieta Hristova; Antoaneta Trifonova Gateva (Metabolites)
Background: Diabetic autonomic neuropathy (DAN) is a severe complication of diabetes that affects the autonomic nervous system, impacting cardiovascular, gastrointestinal, genitourinary, and other systems. This study examines the levels of three potential biomarkers—DEFA1, progranulin, and NRG4—to assess their diagnostic and prognostic value in DAN patients. Methods: This observational, single-center study included 80 patients with type 2 diabetes. Clinical data and laboratory results were collected, and serum levels of DEFA1, progranulin, and NRG4 were measured using ELISA. The presence of DAN was assessed using Ewing’s tests. Statistical analyses included t-tests, Pearson’s correlations, and ROC analysis to explore associations and the predictive values of the biomarkers. Results: Progranulin levels were significantly elevated in patients with DAN compared to those without (p < 0.05), showing a positive correlation with diabetes duration (r = 0.375; p = 0.01) and a significant predictive value for DAN (AUC = 0.666; p = 0.013). DEFA1 and NRG4 levels did not differ significantly between the groups. Progranulin was also higher in patients who were treated with sulfonylureas and GLP-1 receptor agonists and in those with coronary artery disease. Conclusions: Progranulin emerges as a potential biomarker for the presence and severity of DAN, correlating with disease duration and autonomic dysfunction. While DEFA1 and NRG4 showed no significant association, the findings underscore the importance of further exploring the inflammatory pathways in DAN. Progranulin measurement could enhance early diagnosis and personalized management of autonomic neuropathy in diabetes.